PEMETAAN PEMASARAN ABON IKAN TUNA (Thunnus Sp) (Suatu Kasus pada Usaha Karya Mandiri “ Bu Bedah” Desa Muara Kecamatan Wanasalam - Kabupaten Lebak - Banten) - Bukhari, Ahmad; Krisdianto, Nanang (JURNAL AGRIBISNIS TERPADU, 2017)
This research is to describe the marketing mapping abon of tuna fish by using quantitative mapping, market mapping, price mapping, and traffic mapping. This study used survey method to determine the location of the intentionally (purposive) that is in Business Karya Mandiri "Bu Bedah" Muara Village. Population in this study is the production abon of tuna fish Business of Karya Mandiri "Bu Bedah" Muara Village Wanasalam Lebak Banten. Research use descriptive analysis method where data analyzed by describing collected data. Respondent method taking by snowball sampling. Result of the research 1) The quantitative mapping that total production abon of tuna fish in Business Karya Mandiri "Bu Bedah" is 300 kg / month. 2) Market mapping abon of tuna fish conducted in the market area and outside area. 3) Price mapping abon of tuna fish in Business Karya Mandiri "Bu Bedah". For the price abon of tuna fish to a wholesaler at the price of Rp.140.000 / kg, the price abon of tuna fish to retailers according of the size, the size of 90 grams with the price of Rp. 12.000 and size 140 gram with price Rp. 22,000. The price abon of tuna fish to the consumers the varied in according with the size, the size of 90 grams with the price of Rp. 15.000 and size 140 gram with price Rp. 25.000. With the brand "Bu Bedah". Large traders sell with retailers price Rp. 35,000 with the brand "Sarinah". While retailers (giant, carefour, and hypermart) sell abon to consumers price Rp. 48.900. 4)  Traffic mapping used in the delivery of product abon of tuna fish using four-wheeled vehicles and motorcycles. Delivery time in the morning and evening.